Implementasi Metode Fuzzy-AHP Pada Sistem Penunjang Keputusan Untuk Menentukan Guru Berprestasi Berbasis Web (Studi Kasus: Madrasah Aliyah Syekh Mubarok) - Ahmad Manhatul Irfan; Saprudin (CV. Multi Kreasi Media, 2022)
The process of selecting outstanding teachers at the school level is still done conventionally, namely based on personal observations of the teachers concerned, and only based on certain criteria. Observation or Observation Method Observation method is a data collection technique by conducting direct observations of the object being studied and recording related events. Interview. Method The interview method is the acquisition of data by holding direct conversations and questions and answers that have to do with the object being studied. Literature Study Methods Literature study is a technique to find data related to research sourced from books and documents in the form of journals, related thesis needed to support system development. Documentation Method This method is used to find out the processes that have been carried out by MA Sheikh Mubarok System Development. Methods System development is the preparation of a new system to replace the old system as a whole or improve the existing system. So the appropriate development for the system created is using the Waterfall method. Based on the problems and problem solving solution plans above, in writing this thesis the author takes the title